Constructing the New Capital City: Chinese Architects and the Urban Plan of Nanjing during the Republican Era (1927-1949) - Wang, Shu (International Planning History Society Proceedings, 2024)
Based on ongoing postgraduate (MPhil) research, the conference presentation discusses features of modernization, identity, and nationhood within the narrative of Nanjing’s urban planning during China's Republican Era（1927-1949）. It accomplishes this through attention to native architect-planners, e.g. Lu Yanchi （呂彥直）, Doon Dayu （董大酉）, and Robert Fan （范文照）. They were assistants of Henry Murphy, the chief consultant of the Capital Plan. The presentation will utilize primary Chinese sources such as newspapers, manuscripts, archives, documents, and old photographs, and so intends to analyze the works of the young Chinese architect-planners together with the political intentions and intellectual influences upon how the built fabric was shaped and meant. As the capital city of Republican China, Nanjing was to become the symbol of ‘the modern country’. Its form and density were to be affected by considerations about the nature of the citizenry, the contemporary political atmosphere, Chinese traditional and modern culture, and financial funding. Collectively, these elements affected the development of Nanjing during the Republican Era and contributed in different way to its plan's successes and failures.